Hydroponic-Based Wastewater Treatment for Reuse: A Comparative Assessment of System Efficiency and Performance - Haddad, Marwan (Journal of Environmental Science and Engineering Technology, 2024)
This study assesses the performance and applicability of various pilot-scale hydroponic systems for the dual purpose of treating domestic wastewater and supporting agricultural food production. A comparative analysis of water quality improvement, based on removal efficiencies for TSS, TDS, BOD, COD, TN, and TP, identified the NFT and vertical gradual flow hydroponic systems as the most effective among the five systems evaluated. These systems demonstrated superior contaminant removal rates while promoting plant growth with targeted nutrient additions and addressing key challenges such as salinity and heavy metal accumulation. Key insights revealed improved crop productivity in specific contexts: faba beans and green peas thrived in NFT setups, while musk melons exhibited resilience to salinity levels up to 3000 ppm, making them suitable for saline regions. Additionally, the ability of certain crops to hyperaccumulate heavy metals offers a phytoremediation pathway, further enhancing the environmental benefits of hydroponic systems. Hydroponic setups were shown to produce high agricultural yields with minimal environmental impact, adaptable to both urban and rural contexts. A comprehensive SWOT analysis underscored the NFT system's significant strengths, including sustainability, cost-effectiveness, and environmental health benefits, while identifying minimal weaknesses and threats. Conversely, container and vertical flow systems demonstrated limited applicability due to higher operational challenges and fewer advantages. These findings support the NFT hydroponic system as a robust, scalable solution for wastewater treatment and agricultural production, with significant potential for continuous research, technological innovation, and broader application across diverse environmental and agricultural scenarios.